PCREB expression in human tissues from epilepsy surgery. (28th May 2020) - De Santis, Dalia; Rossini, Laura; Tassi, Laura; Didato, Giuseppe; Tringali, Giovanni; Cossu, Massimo; Bramerio, Manuela; Padelli, Francesco; Regondi, Maria Cristina; Colciaghi, Francesca; Aronica, Eleonora; Spreafico, Roberto; et al.
Abstract: Objective: Activity‐dependent changes have been reported in animal models and in human epileptic specimens and could potentially be used as tissue biomarkers to evaluate the propensity of a tissue to generate seizure activity. In this context, cAMP‐response element binding protein (CREB) activation was specifically reported in human epileptic foci and related mainly to interictal spike activity. To get further insights into CREB activation in human epilepsy, we analyzed pCREB expression on brain tissue samples from patients who underwent surgery for drug‐resistant focal epilepsy, correlating this expression with intracranial stereo–electroencephalography (SEEG) recording in a subgroup. Methods: Neocortical specimens from patients with neuropathological diagnosis of no lesion (cryptogenic), malformations of cortical development, mainly type II focal cortical dysplasia (FCD), and hippocampi with and without hippocampal sclerosis have been analyzed by immunohistochemistry. Peritumoral cortex from non‐epileptic patients and autoptic samples were used as controls, whereas rat brains were used to test possible loss of pCREB antigenicity due to fixation procedures and postmortem delay. Results: pCREB was consistently expressed in layer II neuronal nuclei in regions with normal cortical lamination both in epileptic and non‐epileptic surgical tissues. In patients with SEEG recordings, this anatomical pattern was unrelated to the presence of interictal spike activity. Conversely, in the core of type II FCD, as well as in other developmental malformations, pCREB was scattered without any laminar specificity. Furthermore, quantitative data did not reveal significant differences between epileptic and non‐epileptic tissues, except for an increased immunoreactivity in the core of type IIB FCD lesion related mainly to reactive glial and balloon cells. Significance: The present data argue against the reliability of pCREB immunohistochemistry as a marker of epileptic focus but underscores its layer‐related expression, suggesting a potential application in the study of malformations of cortical development, a wide range of diseases arising from perturbations of normal brain development.